A Comparative Study of Product Costing by Using Activity-Based Costing (ABC) and Time-Driven Activity-Based Costing (TDABC) Method - Nurul Farahin, Zamrud; Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Filzah Lina, Mohd Safeiee (Springer, 2019)
This research study revolves around a case study company, which manufactures electric and electronics products. The objective of this work is to compare Activity-Based Costing (ABC) and Time-Driven Activity-Based Costing (TDBAC). This work began by collecting data related to the production costs of a selected product. The product has been selected based on the volume of production which is high and continuous. The next phase in this study involved analyzing costs using ABC and TDABC method. These costing methods are compared on the accuracy and the unused capacity. The results showed that TDABC improves the costing accuracy and helps reducing waste by introducing time equation on the production cost structure. Finally, it is concluded that from this comparative study, TDABC would be beneficial to the company in a competitive environment and future further studies on product costing.